1992
DOI: 10.1017/s1049023x00039777
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up and Outcome of Patients Who Decline or Are Denied Transport by EMS

Abstract: Introduction:In recent years, several authors have begun to address the medical and legal risks associated with patients refusing or being refused transport by emergency medical services (EMS) systems. However, data regarding patient outcomes still are lacking.Purpose:The purpose of this study was to determine: 1) why patients are not transported; and 2) the subsequent outcome of these patients.Setting:A busy, suburban, volunteer EMS service with indirect medical control, but no guidelines for non-transport of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 7 publications
1
55
0
Order By: Relevance
“…• Unplanned medical attention after being seen/relapse EMS calls 17,43,48,49,[58][59][60]68 • Define ideal length of time to follow patients, for example:…”
Section: Outcome Measures Reported On Alternatives To Ems Dispatchmentioning
confidence: 99%
See 1 more Smart Citation
“…• Unplanned medical attention after being seen/relapse EMS calls 17,43,48,49,[58][59][60]68 • Define ideal length of time to follow patients, for example:…”
Section: Outcome Measures Reported On Alternatives To Ems Dispatchmentioning
confidence: 99%
“…• Patient satisfaction 16,17,25,26,49,51,[57][58][59][60][66][67][68] • Collect by follow-up patient interview. 16,26,51,53 • Patient perception of care received 51,53 • Collect by follow-up patient interview.…”
Section: ;17(5)mentioning
confidence: 99%
“…In 1992, Zachariah et al 39 reported outcomes of patients who declined or who were denied transport by EMS personnel in Harris County, Texas. In a system without a strict written protocol defining the appropriate criteria for EMS provider decision to not transport, 50 patients were denied transport, and 11 (22%) of those patients subsequently required hospitalization.…”
Section: Ems Determinations Of Medical Necessity For Ambulance Transportmentioning
confidence: 99%
“…In a system without a strict written protocol defining the appropriate criteria for EMS provider decision to not transport, 50 patients were denied transport, and 11 (22%) of those patients subsequently required hospitalization. 39 In 2001, Pointer et al 40 reported paramedic determinations about medical necessity in Alameda County, California, when using a set of written guidelines, and found that 113 of the 1,180 patients in the data set (9.6%) had been undertriaged based on a reference standard of physician determination that the patient should be transported directly to the emergency department (ED). In 2003, Gratton et al 41 reported paramedic determinations of medical necessity in Kansas City, Missouri, where paramedics used a structured, five-item screening form.…”
Section: Ems Determinations Of Medical Necessity For Ambulance Transportmentioning
confidence: 99%
“…Admission rates to the hospital following patient-initiated refusal of EMS transport range from 6% to 13%. [1][2][3] Although in some cases it may be safe for patients to refuse transport, 4 the legal risk to providers in inappropriate instances is well documented. 5,6 Prior to allowing a patient to refuse transport, it must be determined whether the patient is capable of making this decision.…”
mentioning
confidence: 99%